Ground Response to High Horizontal Stresses during Longwall Retreat and its Implication on Longwall Headgate Support - Peter Zhang; Dave Gearhart; Mark Van Dyke; Daniel Su; Essie Esterhuizen; Berk Tulu (International Conference on Ground Control in Mining, 2018)
"Roof falls in longwall headgate can occur when weak roof and high horizontal stress are present. To prevent roof falls in the headgate under high horizontal stress, it is important to understand the ground response to high horizontal stress in the longwall headgate and the requirements for supplemental roof support. In this study, a longwall headgate under high horizontal stress was instrumented to monitor stress change in the pillars, deformations in the roof, and load in the cable bolts. The conditions in the headgate were monitored for about six months as the longwall face passed by the instrumented site. The roof behavior in the headgate near the face was carefully observed during longwall retreat. Numerical modeling was performed to correlate the modeling results with underground observation and instrumentation data and to quantify the effect of high horizontal stress on roof stability in the longwall headgate. This paper discusses roof support requirements in the longwall headgate under high horizontal stress in regard to the pattern of supplemental cable bolts and the critical locations where additional supplemental support is necessary.INTRODUCTIONLongwall mining is the primary underground coal mining method in the United States and currently accounts for more than 60% of the underground coal production. The longwall headgate, as a passageway for the longwall crew, intake air, material supplies, and coal belt transportation, is critical for both safety and continuous production of the longwall panel. A roof fall in the longwall headgate would not only result in substantial interruption of production but could potentially cause injuries or fatalities. Rehabilitation of failed roof in the headgate would also expose miners to the risk of injuries. Roof falls in the headgate, though infrequent, mostly occur in the belt entry near the face. Considerable research has been conducted to determine the effects of various factors on headgate roof stability, as well as effective measures to support the roof in longwall mines in the Pittsburgh seam (Mark, Mucho, and Dolinar, 1998; Chen et al., 1998; Su and Hasenfus, 1995; Su, Thomas, and Hasenfus, 1999; Su, Morris, and McCaffrey, 2002; Su, Draskovich, and Thomas, 2003; Hasenfus and Su, 2006; Van Dyke et al., 2015). Previous studies have demonstrated that high horizontal stress and transitional roof geology are primary factors that cause headgate roof failure. These studies also showed that panel orientation, retreat direction, pillar sizes, and roof support played an important role in the stability of a headgate.In underground coal mines located in the eastern United States, the magnitude of the maximum horizontal stress is typically three times greater than the vertical stress, and about 40% greater than the minimum horizontal stress. Mark, Mucho, and Dolinar (1998) studied seven cases of headgate failures caused by high horizontal stress in different coal seams in the United States and stated that roof stability is affected, to a large extent, by rock type, entry orientation, and longwall orientation. The effects of horizontal stress can be summarized in these statements: (1) A laminated roof is very vulnerable to high horizontal stress. (2) Entries that are aligned with the maximum horizontal stress will suffer less damage on development than those perpendicular to it. (3) Horizontal stress concentration and relief depends on panel orientation, the direction of retreat, and the sequence of longwall panel extraction."